Mothering in East Asian communities : politics and practices - Duncan, Patti, 1970-; Wong, Gina, 1971- (Demeter Press, 2014)
In Mothering in East Asian Communities, Duncan and Wong seamlessly rupture a homogenous identity category--that of the ""tiger mom."" The editors invoke the works of diverse contributors who critically challenge essentialized identity categories and racialized and sexualized experiences of women of color within the institution of motherhood and practices of mothering. Here, the edited volume grapples with globalization, transnationalism, and capitalism with an East Asian ethno-racial-cultural context. Duncan and Wong offer a personal and political analysis of motherhood that is socially and cu